Comparative genomics reveals different population structures associated with host and geographic origin in antimicrobial‐resistant Salmonella enterica. (27th April 2020) - Liao, Jingqiu; Orsi, Renato Hohl; Carroll, Laura M.; Wiedmann, Martin
Summary: Genetic variation in a pathogen, including the causative agent of salmonellosis, Salmonella enterica, can occur as a result of eco‐evolutionary forces triggered by dissimilarities of ecological niches. Here, we applied comparative genomics to study 90 antimicrobial resistant (AMR) S. enterica isolates from bovine and human hosts in New York and Washington states to understand host‐ and geographic‐associated population structure. Results revealed distinct presence/absence profiles of functional genes and pseudogenes (e.g., virulence genes) associated with bovine and human isolates. Notably, bovine isolates contained significantly more transposase genes but fewer transposase pseudogenes than human isolates, suggesting the occurrence of large‐scale transposition in genomes of bovine and human isolates at different times. The high correlation between transposase genes and AMR genes, as well as plasmid replicons, highlights the potential role of horizontally transferred transposons in promoting adaptation to antibiotics. By contrast, a number of potentially geographic‐associated single‐nucleotide polymorphisms (SNPs), rather than geographic‐associated genes, were identified. Interestingly, 38% of these SNPs were in genes annotated as cell surface protein‐encoding genes, including some essential for antibiotic resistance and host colonization. Overall, different evolutionary forces and limited recent inter‐population transmission appear to shape AMR S. enterica population structure in different hosts and geographic origins.